1987
DOI: 10.1116/1.574434
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in magnetrons

Abstract: The current conduction processes in a magnetron sputtering diode have been the subject of discussion since the origination of the device. Several techniques have been used to study these conduction processes. Langmuir probe measurements of electron temperature, density, and plasma potential show clear evidence of a positive space-charge sheath. The magnitude of the E×B drift current, determined by measuring the magnetic field induced by the current, is suggestive of Bohm diffusion as the principle means for el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…Classical theory of diffusion and electrical conductivity using collisions to move electrons across the magnetic field, or Bohm diffusion, usually results in j H /j D values of about 16-35 [9,10]. Thus, a low j H /j D value indicates that electron transport across the magnetic field lines is more efficient in the HIPIMS case than can be explained by standard theory.…”
Section: Introductionmentioning
confidence: 91%
“…Classical theory of diffusion and electrical conductivity using collisions to move electrons across the magnetic field, or Bohm diffusion, usually results in j H /j D values of about 16-35 [9,10]. Thus, a low j H /j D value indicates that electron transport across the magnetic field lines is more efficient in the HIPIMS case than can be explained by standard theory.…”
Section: Introductionmentioning
confidence: 91%
“…In dcMS, measurements of J ϕ / J D give typical values in the range 8 < ω ge τ c < 30 [26,27], which is often referred to as the Bohm regime. Note that for the upper limit reference 26…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been found that the cross-conductivity, governing the transport of charged species, is much higher for HiPIMS [16,17,18,19] than for DCMS [20,21]. It is therefore expected that there is a transition from an anomalously high HiPIMS crossconductivity to a lower DCMS Bohm conductivity as the current approaches the plateau-level in the pulse.…”
Section: Lundin Et Almentioning
confidence: 99%